Crowdsourcing in Support of BNT Public Function - Cholakova, Maria (Sledva : NBU Journal of Humanities and Arts, 2020)
The text is driven by the concept of crowdsourcing and seeks its application in support of the public function of the Bulgarian National Television. The author develops concrete suggestions how to implement user-generated content for the benefit of the public media content.